PELATIHAN DAN PENDAMPINGAN MENGGAMBAR 3D MENGGUNAKAN SOFTWARE SKETCHUP DALAM UPAYA MENINGKATKAN KOMPETENSI ANGGOTA KOMUNITAS ARCHASENA TULUNGAGUNG - Saputri, Diyah Ayu (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
The advancement of 3D technology, particularly in relation to Sketchup, has had a significant impact on the professional world, especially in the fields of design, architecture, construction, and product development. One way is through the use of Sketchup, which enables designers to create accurate and detailed 3D models of buildings and interiors. Considering the challenges and opportunities available, it is necessary to prepare students to compete according to the demands of the workforce. Based on the identification of this situation, the team needs to conduct training and mentoring in 3D drawing using Sketchup. The aim of this service is to enhance participants' understanding of soft skills by introducing 3D drawing using Sketchup. In this activity, participants are given a project to create a 3D model of a simple house with predetermined floor plans and basic views. Participants are given the freedom to create the building facade according to their creativity, allowing them to apply their understanding of aesthetics in building design. Training data indicates a significant improvement in participants' understanding from before to after the training and mentoring, reflected in the high enthusiasm of participants in participating in all activities from start to finish. This indicates that the participants have a better understanding of Sketchup usage after completing the training. Additionally, participants produce simple building 3D model results shown by exporting 2D graphics.